Drugs for preventing postoperative nausea and vomiting in adults after general anesthesia: An abridged Cochrane network meta‐analysis. Issue 3 (27th May 2021) - Weibel, Stephanie; Pace, Nathan L.; Schaefer, Maximilian S.; Raj, Diana; Schlesinger, Tobias; Meybohm, Patrick; Kienbaum, Peter; Eberhart, Leopold H. J.; Kranke, Peter
Abstract: Objective: In this abridged version of the recently published Cochrane review on antiemetic drugs, we summarize its most important findings and discuss the challenges and the time needed to prepare what is now the largest Cochrane review with network meta‐analysis in terms of the number of included studies and pages in its full printed form. Methods: We conducted a systematic review with network meta‐analyses to compare and rank single antiemetic drugs and their combinations belonging to 5HT₃‐, D₂‐, NK₁‐receptor antagonists, corticosteroids, antihistamines, and anticholinergics used to prevent postoperative nausea and vomiting in adults after general anesthesia. Results: 585 studies (97 516 participants) testing 44 single drugs and 51 drug combinations were included. The studies' overall risk of bias was assessed as low in only 27% of the studies. In 282 studies, 29 out of 36 drug combinations and 10 out of 28 single drugs lowered the risk of vomiting at least 20% compared to placebo. In the ranking of treatments, combinations of drugs were generally more effective than single drugs. Single NK1 receptor antagonists were as effective as other drug combinations. Of the 10 effective single drugs, certainty of evidence was high for aprepitant, ramosetron, granisetron, dexamethasone, and ondansetron, while moderate for fosaprepitant and droperidol. For serious adverse events (SAEs), any adverse event (AE), and drug‐class specific side effects evidence for intervention effects was mostly not convincing. Conclusions: There is high or moderate evidence for at least seven single drugs preventing postoperative vomiting. However, there is still considerable lack of evidence regarding safety aspects that does warrant investigation.